Comparing multivalent cross-linked Sodium Alginate/ Montmorillonite beads containing Curcumin or Cayenne Pepper as drug carriers and their antimicrobial resistance - Shionainn Traynor; Shubham Sharma (SURE Journal: (Science Undergraduate Research Experience Journal))
The aim of the following work was to investigate and compare curcumin and cayenne pepper in microbeads composed of sodium alginate (SA) crosslinked with montmorillonite (MMT) to act as drug carriers and their antimicrobial resistance. The microbeads were prepared through ion-exchange in multivalent solutions of CaCl2, MgCl2 and AlCl3. The microbeads were characterized by Scanning Electron Microscopy (SEM), Energy Dispersive X-ray analysis (EDX) and the time required for intercalation of curcumin and cayenne pepper with MMT. Simulated intestinal fluid (pH 7.3) and gastric fluid (pH 1.2) at 37°C were used for comparison in swelling studies. Gram-positive S. aureus and Gram-negative E. coli were used for antimicrobial resistance comparison of the multivalent microbeads containing curcumin and cayenne pepper. The results found that curcumin took less time to intercalate with MMT compared to cayenne pepper. Swelling results indicated that pH played a direct role in the uptake of water in the beads with pH 1.2 causing the least amount of water uptake. It was also observed from these results that the MgCl2 beads had the greatest swelling degree and the AlCl3 beads had the lowest swelling degree in both pH1.2 and pH 7.3. EDX results provided information on the elemental composition of the microbeads. SEM results showed the MgCl2 microbeads for both curcumin and cayenne pepper, appeared the roughest allowing for greater water uptake, while the AlCl3 microbeads had a smoother surface leading to less water uptake which correlated with the swelling measurement results. The antimicrobial tests showed the AlCl3 beads for both curcumin and cayenne pepper had the greatest zones of inhibition with curcumin providing the best resistance. The combined results suggest that the beads produced may be best suited for intestinal drug delivery with the curcumin AlCl3 beads providing the overall best results for antimicrobial resistance and drug carrying ability.